Замок князів Чорторийських у Клевані: етапи становлення, планування та забудова - Прищепа, Б.А. (Археологія і давня історія України, 2022)
У статті на основі аналізу писемних джерел
виділено три етапи будівництва Клеванського замку та розглянуто його планування. На першому
етапі (перша чверть ХVІ ст.) князь Федір Михайлович Чорторийський починає будівництво замку
на старому городищі, де, можливо, вже знаходився
господарський двір. На другому етапі (друга чверть
ХVІ ст.), через конфлікт з Радзивілами, будівництво було припинене, але замок функціонував і місто розвивалось. На третьому етапі (60-ті роки ХVІ ст.) князь Іван Федорович Чорторийський завершив будівництво замку. Based on a comprehensive analysis of written, archaeological
and architectural sources the article considers
the main stages of Klevan castle development,
and considers its planning and buildings. According to
archeological sources, the site of the settlement of the
Kyiv Rus period was used to build the castle. According
to the written sources, there were three stages of the
erection of the castle. In the first stage (the first quarter
of the 16th century), Prince Fedir Mykhailovych Czartoryski
began the construction of a castle on the old settlement
site, where, perhaps, there had already been a
farmstead. In the second stage (the second quarter of
the 16th century), due to the conflict with Radziwills,
the construction was stopped but the castle functioned
and the settlement was developed. In the third stage
(the 60s of the 16th century), Prince Ivan Fedorovych
Czartoryski completed the construction of the castle.
The Klevan castle consisted of two parts — a citadel
and the adjacent settlement. The information on the
castle planning is contained in the inventories of 1700
and 1709. The earliest description of 1609 describes
the defense, housing, religious and economic facilities
in the territory of the citadel. It was surrounded by a
wall, had two brick towers and a wooden one. Most
of the buildings were located on the perimeter of the
fortifications; the central part housed the princes’ palace
and a church. According to the inventories of 1700
and 1709, the settlement was located to the north and
east of the citadel and occupied the territory on the hill
where now the Church of the Nativity of Christ is located
and, probably, the area occupied by estates on
Horodyshche street. The citadel was surrounded by a
rampart and oak fence; there was a chapel and a garden
around it, outbuildings, the Greek-Catholic Church
of the Nativity, and the entrance gate. The analysis of
the planning, fortifications and buildings of the Klevan
castle allows to conclude that in the last third of the
16th — early 17th century, it was one of the most powerful
private castles in Volhynia.